2008
DOI: 10.1053/j.semnuclmed.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging-Based Radiobiological Dosimetry

Abstract: Targeted radionuclide therapy holds promise as a new treatment against cancer. Advances in imaging are making it possible to evaluate the spatial distribution of radioactivity in tumors and normal organs over time. Matched anatomical imaging such as combined SPECT/CT and PET/CT have also made it possible to obtain tissue density information in conjunction with the radioactivity distribution. Coupled with sophisticated iterative reconstruction algorithims, these advances have made it possible to perform highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 69 publications
2
54
0
2
Order By: Relevance
“…4,12 The average measured tumor half-times are on the order of the physical decay half-life of 46.5 hours, confirming previously published results, 28 although with a much greater variability than with the WB results. As a first approximation, the 153 Sm-EDTMP binds to the tumor site such that there is relatively little biological clearance, unlike highmolecular-weight antibody agents, which have a more prolonged uptake time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…4,12 The average measured tumor half-times are on the order of the physical decay half-life of 46.5 hours, confirming previously published results, 28 although with a much greater variability than with the WB results. As a first approximation, the 153 Sm-EDTMP binds to the tumor site such that there is relatively little biological clearance, unlike highmolecular-weight antibody agents, which have a more prolonged uptake time.…”
Section: Discussionsupporting
confidence: 79%
“…Planar image quantification, which has long been the principal means of activity quantification used as an input into the calculation of absorbed dose, 1 requires an extensive array of methodological adjustments for scatter correction, [2][3][4][5] attenuation, [6][7][8] septal penetration, and, most recently, deadtime correction for whole-body (WB) images involving the relative motion between the camera and imaged object, 9 with an end result that is still controversial. In particular, He et al 10,11 showed, in the context of phantom studies, an absolute uncertainty of 30% in planar quantification compared with 5% using single-photon emission computed tomography (SPECT) images; the relative quantification, that is, determination of kinetic parameters, is considered to be more reliable 4,12 as the errors from scatter, septal penetration, and attenuation generally cancel out from one time point to the next for the same imaged object. As yet, no such comparison has been extended to clinical data where certain methodological components present a much greater challenge and the potential for increased uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear medicine imaging is often used for the quantification of the dosimetric calculations. Much software have been developed for the calculation of the absorbed radiation doses to organs and tumors based on serial 3D imaging and anatomical information from computed tomography (CT) or magnetic resonance imaging (MRI) (Sgouros et al, 2008). Accurate quantification of -camera and positron-emission tomography (PET) images and measurements of for example the radioactive blood content over time, are also becoming increasingly important for many diagnostic nuclear medicine procedures.…”
Section: Radiation Dosimetry In the Clinical Situationmentioning
confidence: 99%
“…Assessment of the absorbed doses in the target and critical tissues is also needed to optimize the activity to inject (5)(6)(7)(8)(9). Until recently, investigators focused on the major emission of 90 Y (i.e., b-rays) that was imaged with SPECT using the bremsstrahlung x-rays, the energy spectrum of which is continuous.…”
mentioning
confidence: 99%